PUBLIC POLICY AND PUBLIC POLICY RESISTANCE: Critical Analysis toward Badung Regency Government Policy in Operating Mengwi Terminal - Muhammad Ali Azhar (Universitas Wahid Hasyim Semarang, 2013)
Abstract Policy is an instrument of government, not just in the sense of government as state officials, but also various forms of governance that touches both private institutions, businesses, and civil society. If they are not involved in government policy, some institutional forms as mention above will be resistant to the policy. This paper reviews resistance about the government's policy in Mengwi terminal operations. Start at 22nd of June 2012, through decree number SK.1543/AJ.106/DR JD in 2012, the government of Badung regency which is related to its ranks; government of Denpasar, Bali's provincial and central government decided that Mengwi terminal operated. However, operationally decision, not necessarily get a positive response from the object being regulated. It is caused, they are not engaged by the Badung regency government in their policy development terminal. As a result, the terminal is operated only half-heartedly by the holders discretion. Key words : policy, model and policy approaches, resistance policy